Contribuições fitotécnicas para o desenvolvimento da couve-chinesa e flor do deserto em região litorânea do nordeste brasileiro - Dantas, Lydio Luciano de Góis Ribeiro (2015)
The development of techniques from the field of knowledge of the area known as Phytotechny, has contributed to the qualified production. Works that involve from seedling production to the application of stimulating substances to plant size reduction have been successfully carried out, which has enabled the production of vegetables in previously unexplored areas. Within this context, this paper presents the results of two separate researches, both developed with the intention of generating new information concerning species under high and low latitude cultivation. In general, for the seedling production, the research results have shown that larger containers produce better results for seedlings’ development. However, these containers also present some disadvantages. Since they are larger, they take more room in the nursery and need higher quantities of substrate, increasing the costs. Within this context, we tried to evaluate the development of Chinguensai seedlings which were planted in trays with different volumes, filled with different substrate formulations. For such, we performed two trials, both using randomized complete blocks (RCB). The first trial was done in a 4x4 factorial scheme, four formulations of substrate containing coconut powder, carbonized rice hull and vermicompost, in the following proportions: S1 (1:1:1), S2 (0:1:1), S3 (1:0:1) and S4 (0:0:1), and four evaluation dates: 22; 27; 34 and 41 days after sowing (DAS). As for the second trial, it was done in a 3x4 factorial scheme, three types of containers: 11; 18 and 31 cm³, and the same evaluation dates. The substrate, made of vermicompost in a cell tray of 31 cm³, provided seedlings which were more vigorous and able to be transplanted after 41 DAS. As for the use of paclobutrazol (PBZ), we tried to evaluate the effects of different PBZ doses in the development and in the quality of Adenium for the aesthetical standardization for the potted plant market. The experiment was carried out in a RCB vegetation house, composed of six concentrations: 0; 5; 10; 20; 40 e 80 mL of the PBZ active ingredient, in one single application with four repetitions. The results were submitted to ANOVA at the levels of p < 0.01 and p > 0.05 of significance, and the quantitative data average was employed through regression analysis by using the ASSISTAT software. The curve fitting procedure adjustment for the treatment factors was done by using the Table Curve 2D software. We verified some significance for the anthocyanin variable, where PBZ impaired its concentrations present in the leaf tissues. The dose of 80 mL of PBZ reduced the Length of Aerial Part in 37.29% in relation to control. However, the phytotoxic effects caused by PBZ hinder its use in commercial production.